Oscillation Theorems for Second Order Delay Equations - Sahala Nababan (Institute for Research and Community Services (LPPM) ITB, 1976)
Abstract. Recently, oscillation criteria for certain second order delay differential equations have been substantially studied by [2], [3], [5], and others. In this paper, we generalize and extend some of their results to a more general delay differential equation of the type (r(t)y'(t))' + F (t,y(t),y(g(t))) = 0t â‰¥ Î± > 0